Rehabilitative Sentencing for Narcotics Addicts within the Framework of National Law and Maqasid Syari’ah - Andri Winjaya Laksana; Ida Musofiana; Alwan Hadiyanto; Ahmed Kheir Osman; Ahmed Rabie Hassan (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2026)
Narcotics-related crimes are classified as extraordinary crimes that threaten not only individual lives but also the broader fabric of society. Narcotics addicts, while legally considered offenders, are in fact self-victimizing individuals whose behavior is driven by dependency and loss of self-control. Rehabilitative sentencing offers a progressive alternative to punitive approaches by prioritizing treatment, recovery, and reintegration over retribution. This study aimed to critically examine the implementation of rehabilitative sentencing for narcotics addicts within Indonesia’s legal framework, while simultaneously analyzing its compatibility with the higher objectives of Islamic law (maqasid syari’ah). moreover, this study adopts a socio-legal (juridical-sociological) approach, combining normative legal analysis with empirical insights from social behavior and community responses. It explores how rehabilitative sentencing is implemented within Indonesia’s legal framework and assessed through the lens of Islamic criminal law. Indonesian Law No. 35 of 2009 on Narcotics, along with supporting regulations, formally provides mechanisms for rehabilitation. However, sociological findings reveal persistent challenges in practice, including legal stigma, institutional capacity gaps, and public skepticism toward non-custodial measures. Meanwhile, Islamic criminal law, through the taʿzir framework, supports rehabilitation as a form of moral and social correction, rooted in the higher objectives of Islamic law (maqasid syari’ah), particularly the protection of life (hifz al-nafs), intellect (hifz al-‘aql), and public welfare (hifz al-maslahah al-‘ammah). The study concludes that successful implementation of rehabilitative sentencing requires not only regulatory readiness but also societal acceptance and alignment with ethical-legal values grounded in both national and Islamic legal traditions.